Efektivitas Senam Mata untuk Mengurangi Tingkat Kelelahan Mata pada Pekerja Rambut Palsu - Febri Mahalinda Maisal; Luh Putu Ruliati; Noorce Christiani Berek; Andreas Umbu Roga; Jacob Matheos Ratu (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
Making wigs requires high eyes concentration and precission, because it has a work with small object and is done monotonously. If it is done for a certain period of time, it will cause tension in the eye’s muscles, which can cause eyes fatigue. Efforts to prevent eyes fatigue were done by doing eye exercises in order to improve the ability of the nerves and eyes muscles. This study aimed to analyze the differences in the average value of eyes fatigue between the intervention group and the control group to reduce the level of eyes fatigue in the wig’s workers. This research is an experimental study using randomized pre-posttest control group design. Research was conducted at CV. Dona Mandiri, Kupang City, with the population of 79 people and chosen by simple random allocation. The study subjects numbered 17 people in the intervention group and 17 people in the control group. The level of eye fatigue was measured using an eyes fatigue questionnaire consisting of 10 questions about symptoms of eyes fatigue. Data analysis using independent sample T-test. The results showed that the signifikan difference in the average value of eye fatigue in the intervention group and the control group amounted to 9.412 (p<0.05). It concluded that eyes exercises could reduce the level of eyes fatigue in wigs hair workers.